53rd National Meeting of the Italian Society of Biochemistryand Molecular Biology (SIB)andNational Meeting of Chemistry of Biological Systems - Italian Chemical Society (SCI - Section CSB) Palazzo dei Congressi di Riccione (23rd - 26th September 2008) (Proceedings e report, 2008)
The 53rd National Congress of the Italian Society of Biochemistry and Molecular Biology (SIB), which will be held in Riccione from 23 to 26 September, is characterised by the elevated scientific level and interdisciplinary interest of the numerous sessions in which it is organised. The Scientific Programme comprises three joint Symposia of the SIB and the Chemistry of Biological Systems section of the Italian Chemistry Society (SCI) on Molecular Systems Biology, Chemistry of Nucleic Acids, Protein and Drug Structure, and Environmental Biotechnology. These Symposia address groundbreaking arguments, making the joint interest of the two societies particularly fascinating; the joint organisation of these events in fact signals the shared intention to proceed along the path of scientific exchange. The topics of the other sessions have been chosen by the Scientific Committee on the basis of their scientific relevance and topicality, with particular attention paid to the selection of the speakers. The SIB sessions will range from Signal Transduction and Biomolecular Targets, Protein Misfolding and its Relationship with Disease, Emerging Techniques in Biochemistry, Gene Silencing, Redox Signalling and Oxidative Stress, Lipids in Cell Communication and Signal Transduction, Mitochondrial Function and Dysfunction.